Systematic review and meta-analysis: Prevalence and possible causes of vitamin D deficiency and insufficiency in pediatric cancer patients. Issue 1 (February 2016) - Revuelta Iniesta, R.; Rush, R.; Paciarotti, I.; Rhatigan, E.B.; Brougham, F.H.M.; McKenzie, J.M.; Wilson, D.C.
Summary: Background and aims: Vitamin D inadequacy is now an internationally recognized health problem and pediatric cancer patients may be at even higher risk than healthy children. We aimed to evaluate primary research to establish the prevalence of vitamin D inadequacy and to explore its possible causes in pediatric cancer patients. Methods: Electronic databases were searched (no restriction-Aug 2013) with no language restrictions and keywords related to cancer and vitamin D. We included studies of patients aged <18 years, diagnosed with and treated for cancer and reporting plasma vitamin D status. Evidence was critically appraised employing the CASP tool. Meta-analysis was performed when appropriate. Results: We included 19 studies, which were mainly of moderate-quality and heterogeneous in the definitions of vitamin D deficiency and insufficiency. The median (range) prevalence of vitamin D deficiency was 14% (0–61.5%) and insufficiency 23% (0–83%). Finally, a significant effect of younger age with vitamin D inadequacy was shown (effect size: −0.132; 95%CI −0.203,  −0.060). Conclusion: There is a possibility of a high prevalence of vitamin D inadequacy in pediatric cancer patients, especially older children, urging the need for high-quality population-based longitudinal studies using standard definitions.